2007
DOI: 10.1083/jcb.200708090
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide RNAi screen reveals multiple regulators of caspase activation

Abstract: Apoptosis is an evolutionally conserved cellular suicide mechanism that can be activated in response to a variety of stressful stimuli. Increasing evidence suggests that apoptotic regulation relies on specialized cell death signaling pathways and also integrates diverse signals from additional regulatory circuits, including those of cellular homeostasis. We present a genome-wide RNA interference screen to systematically identify regulators of apoptosis induced by DNA damage in Drosophila melanogaster cells. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 31 publications
2
71
4
Order By: Relevance
“…This is probably a well-conserved phenomenon across evolution. Yuan and colleagues performed a genome-wide RNAi screen to identify genes that regulate caspase activation in Drosophila (Yi et al, 2007), and they found that many of the genes that regulated apoptosis were genes involved in metabolism; from carbohydrate metabolism to fatty acid synthesis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…This is probably a well-conserved phenomenon across evolution. Yuan and colleagues performed a genome-wide RNAi screen to identify genes that regulate caspase activation in Drosophila (Yi et al, 2007), and they found that many of the genes that regulated apoptosis were genes involved in metabolism; from carbohydrate metabolism to fatty acid synthesis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…This may reflect that inhibition of Drp1 activity is itself lethal or damaging to mammalian cells and/or that Drp1 is only indirectly connected to the activity of Bax and Bak that more centrally mediates programmed cell death. Drp1 impact on Mfn1/2, OPA1, or even Miro-1, an OMM GTPase recently found to mediate caspase activation in Drosophila (Yi et al 2007), may be the key. If death stimuli are so great that Bcl-xL only partially protects cells, Drp1 inhibition may have little effect on cell viability even when an inhibition of cytochrome c release is apparent (Parone et al 2006).…”
Section: Post-translational Modification Of Drp1 Regulates Its Role Imentioning
confidence: 99%
“…In a genome-wide screen for genes required for apoptosis in Drosophila cells, multiple genes directly involved in cellular metabolism, such as genes encoding citrate synthase (CS) and 3-ketoacyl-acyl carrier protein synthase, were found to protect against apoptosis induced by the removal of DIAP1, which is a direct inhibitor of Drosophila caspases (Yi et al, 2007). Additional studies will be needed to identify the exact metabolic changes mediated by the downregulation of these 'housekeeping' genes that protect cells against apoptosis.…”
Section: Metabolic Regulation Of Caspase Activationmentioning
confidence: 99%